2023
DOI: 10.3389/fpls.2023.1114172
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomic profiling of Arabidopsis thaliana roots and leaves reveals complex response mechanisms induced by a seaweed extract

Abstract: Seaweed extracts are a prominent class of biostimulants that enhance plant health and tolerance to biotic and abiotic stresses due to their unique bioactive components. However, the mechanisms of action of biostimulants are still unknown. Here, we have used a metabolomic approach, a UHPLC-MS method, to uncover the mechanisms induced following application to Arabidopsis thaliana of a seaweed extract derived from Durvillaea potatorum and Ascophyllum nodosum. We have identified, following the application of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Epigenetic regulation of secondary metabolism: Plants have developed a sophisticated defense mechanism that utilizes secondary metabolites, such as phenolic compounds and alkaloids, against potential threats from pathogens and herbivores. Emerging research suggests epigenetic regulation also plays a crucial role in producing these compounds [ 154 , 155 , 156 ]. Specifically, studies demonstrate that DM and histone modifications improve the gene modification that produces anthocyanins, a particular phenolic compound that safeguards plants from UV radiation and oxidative stress [ 44 , 154 ].…”
Section: Recent Discoveries Of Plant Epigenetic Regulation In Respons...mentioning
confidence: 99%
“…Epigenetic regulation of secondary metabolism: Plants have developed a sophisticated defense mechanism that utilizes secondary metabolites, such as phenolic compounds and alkaloids, against potential threats from pathogens and herbivores. Emerging research suggests epigenetic regulation also plays a crucial role in producing these compounds [ 154 , 155 , 156 ]. Specifically, studies demonstrate that DM and histone modifications improve the gene modification that produces anthocyanins, a particular phenolic compound that safeguards plants from UV radiation and oxidative stress [ 44 , 154 ].…”
Section: Recent Discoveries Of Plant Epigenetic Regulation In Respons...mentioning
confidence: 99%
“…Some plant studies have shown that exposure to radiation can increase genetic variety, which may help protect ecosystems against environmental changes at low doses [46]. Nevertheless, some studies have observed reduced germination, slowed growth, and lethal effects beyond specific dosage thresholds [47].…”
Section: Environmental Monitoringmentioning
confidence: 99%
“…However, green technologies that use natural materials can reduce these concerns. [138] The integration of nanomaterials into the food chain requires careful consideration of potential long-term effects and public awareness. [34,139] Comprehensive assessments of environmental risks and government guidelines are necessary to regulate the use of nanomaterials in agriculture.…”
Section: Challenges/perspectives Of Advanced Photosystem Engineering ...mentioning
confidence: 99%